LIKUIDITAS KOPERASI PADA SAAT PANDEMI COVID-19 DI KECAMATAN KOTA WAINGAPU - Frengki Diki Takanjanji; Linda Rambu Kuba Yowi (LPPM STIE PERTIBA Pangkalpinang, 2022)
The Covid-19 pandemic has caused the majority of cooperatives in Indonesia to experience liquidity shocks. On the other hand, liquidity greatly affects the sustainability of cooperative operations and if the liquidity of cooperatives is disrupted it will affect the finances of cooperatives. This study aims to analyze the level of liquidity of cooperatives before and during Covid-19, the causes of liquidity problems in cooperatives, and the strategy of cooperatives in overcoming liquidity problems. This type of research is qualitative with research respondents being four treasurers in four savings and loan cooperatives. The data analysis technique used is descriptive qualitative. The results of the study concluded that: (1) The level of liquidity or cash adequacy of cooperatives before Covid-19 increased. While the level of liquidity after the Covid-19 pandemic has decreased, (2) The causes of liquidity problems in cooperatives are due to the decrease in sales turnover of cooperative members as MSME entrepreneurs, taking deposits by cooperative members, and (3) the strategy taken to overcome the liquidity problem of cooperatives is by reducing the number of loans to cooperative members, reducing the number of employees, limiting large-scale savings taking by cooperative members, and increasing capital from the cooperative's head office.